Open Source Data Collection in the Developing World. - Anokwa, Yaw; Hartung, Carl; Brunette, Waylon; Borriello, Gaetano; Lerer, Adam (Computer (00189162), 2009)
The article describes the development of Open Data Kit (ODK), a suite of tools that allows users to own, visualize and share data without the hassles of setting up a maintenance servers. Tools such as ODK Collect, ODK Aggregate, and ODK Manage were released to aid practitioners in collecting rich data sets. The use of ODK by Kenya's Academic Model for the Prevention and Treatment of HIV (AMPATH) to scale the technology of the Home-Based Counseling and Testing (HCT) program is also discussed.